2021
DOI: 10.1155/2021/1622270
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity Derived from Marine Green‐Lipped Mussel Perna canaliculus Extracts in Mice

Abstract: This study investigates the antioxidant activities of lipid, protein, and carbohydrate extracts from the marine mollusk Perna canaliculus. Lipids were extracted using acetone, which was followed by protein extraction using the broad-spectrum enzyme Alcalase and then carbohydrate extraction using cetylpyridinium chloride. Eighty white BALB/c mice were divided into eight groups according to the administered extracts. Groups 1 and 5 were the control and toxin control groups, respectively. Groups 2, 3, and 4 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“… 100 Interestingly, antioxidants in green-lipped mussels were proven to mediate the free radicals, which were the typical indicators in inflamed joints. 101 , 102 Therefore, a variety of injectable materials have been developed to fill the joint cavity, capable of inflammatory factor elimination especially in the liquid form. For instance, Chen’s 103 study demonstrated that GelMA hydrogel implantation combined with CM-SIN injection was a promising strategy for inducing autophagy and ameliorating osteoarthritis cartilage degradation.…”
Section: The Applications Of Mussel Biomimetic Materials In Msdsmentioning
confidence: 99%
“… 100 Interestingly, antioxidants in green-lipped mussels were proven to mediate the free radicals, which were the typical indicators in inflamed joints. 101 , 102 Therefore, a variety of injectable materials have been developed to fill the joint cavity, capable of inflammatory factor elimination especially in the liquid form. For instance, Chen’s 103 study demonstrated that GelMA hydrogel implantation combined with CM-SIN injection was a promising strategy for inducing autophagy and ameliorating osteoarthritis cartilage degradation.…”
Section: The Applications Of Mussel Biomimetic Materials In Msdsmentioning
confidence: 99%
“…Additionally, they have numerous unique scaffolds, which afford more and more inspiration for drug discovery [16][17][18][19][20][21][22][23][24][25]. Though terrestrial plants as well as bacteria have usually been the main resources of natural metabolites, in the last 30 years, marine ecosystems, including their invertebrates, plants, as well as bacteria, have also been the main sources of numerous novel structural metabolites, which are identified as natural marine products [26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%